Annual and semiannual variations of phytoplankton biomass and production in the central Gulf of California estimated from satellite data - Laura Lucero Álvarez-Molina; Saúl Álvarez-Borrego; José Rubén Lara-Lara; SG Marinone (Ciencias Marinas, 2013)
Surface waters of the Midriff Islands region of the Gulf of California persistently have the lowest temperatures (SST) and the highest nutrient concentrations of all surface waters of the gulf. The purpose of this work was to characterize the annual and semiannual variations of satellite-derived SST, chlorophyll a (Chlsat), and phytoplankton production (PP) along transects in Ballenas Channel (transect A), between Ángel de la Guarda and Tiburón islands (transect B), and San Pedro Mártir Basin (SPMB) (transect C). This was done with monthly composites of SST, Chlsat, and PP for 2005 and 2006. Chlsat and PP have annual and semiannual components of variation at the three transects, but the temporal setup is different for each transect. In Ballenas Channel the two maxima occurred in March–June and October, while along transect B in March–May and in late autumn and early winter, and at SPMB in February–May and October–December. The explanation for the differences is in the physical dynamics of these areas. Strong turbulence and stratification caused low Chlsat and PP, and intermediate stratification caused high values for transects A and B. On the eastern side of transect C, upwelling caused the highest Chlsat and PP of our data set (up to 9.7 mg m–3 and 7.8 g C m–2 d–1). Photosynthesis in our study area is not limited by iron. Low summer Chlsat and PP values are caused by strong stratification inhibiting nutrient eddy diffusion from below the thermocline to the euphotic zone. Nevertheless, the summer Chlsat and PP values for the Midriff Islands region (often >1 mg m–3 and >1 g C m–2 d–1) are relatively high.